1993
DOI: 10.1007/bf01316798
|View full text |Cite
|
Sign up to set email alerts
|

Truncated GLP-1 (proglucagon 78?107-amide) inhibits gastric and pancreatic functions in man

Abstract: We studied the effect of intravenous infusion of synthetic truncated GLP-1 (proglucagon 78-107-amide) on fasting and postprandial gastric acid secretion, gastric emptying, and pancreatic secretion of trypsin and lipase in eight normal volunteers using marker dilution and aspiration technique. The infusion resulted in a plasma concentration of 110 +/- 14 pmol/liter (mean +/- SEM). Truncated GLP-1 significantly inhibited postprandial acid secretion by 43 +/- 11% in spite of unchanged plasma gastrin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
402
1
12

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 638 publications
(428 citation statements)
references
References 37 publications
13
402
1
12
Order By: Relevance
“…sensitizes the alpha cell to the suppressive effects of glucose [98]. It may be noted that the magnitude of the decrease in the PG 50 for the AGR arg in response to GLP-1 to is very similar to the increase in this parameter estimated from mean data comparing patients with type 2 diabetes with healthy volunteers (cf. Fig.…”
Section: Acute Effects Of Exogenous and Endogenous Glp-1 On Alpha Celmentioning
confidence: 69%
See 2 more Smart Citations
“…sensitizes the alpha cell to the suppressive effects of glucose [98]. It may be noted that the magnitude of the decrease in the PG 50 for the AGR arg in response to GLP-1 to is very similar to the increase in this parameter estimated from mean data comparing patients with type 2 diabetes with healthy volunteers (cf. Fig.…”
Section: Acute Effects Of Exogenous and Endogenous Glp-1 On Alpha Celmentioning
confidence: 69%
“…7b) occurs. The PG 50 for prestimulus glucagon averaged 15.5±1.0 mmol/l when saline was infused and 11.0±0.8 mmol/l during GLP-1 infusion (p<0.001). Similarly, the PG 50 for AGR arg was 15.5±0.7 mmol/l during saline and 12.1±0.8 mmol/l during GLP-1 (p<0.001).…”
Section: Acute Effects Of Exogenous and Endogenous Glp-1 On Alpha Celmentioning
confidence: 93%
See 1 more Smart Citation
“…Further important effects of GLP-1 include inhibition of gastrointestinal secretion and motility, notably gastric emptying [96,97]. This effect is also desirable in patients with diabetes, because the slower gastric emptying rate reduces postprandial glucose excursions as is evident from the use of another potent gastric inhibitor, amylin, for diabetes treatment [98]; finally, GLP-1 inhibits appetite and food intake.…”
Section: Incretin Hormones As Therapeutic Agentsmentioning
confidence: 99%
“…Furthermore, GLP-1 not only stimulated glucose-induced insulin secretion, but also all steps of insulin biosynthesis and insulin gene expression [31]. GLP-1 also turned out to have powerful effects on gastrointestinal secretion and motility [32,33], and it was shown that inhibition of gastric emptying had strong effects on postprandial glucose excursions [34] in healthy subjects and patients with type 2 diabetes [35]. In addition, GLP-1 was shown to inhibit appetite and food intake, both in healthy individuals [36], and in patients with type 2 diabetes [37].…”
Section: Glp-1 and Diabetes Treatmentmentioning
confidence: 99%